2021
DOI: 10.1101/2021.12.22.473833
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A rhythmically pulsing leaf-spring nanoengine that drives a passive follower

Abstract: Molecular engineering seeks to create functional entities for the modular use in the bottom-up design of nanoassemblies that can perform complex tasks. Such systems require fuel-consuming nanomotors that can actively drive downstream passive followers. Most molecular motors are driven by Brownian motion, but the generated forces are scattered and insufficient for efficient transfer to passive second-tier components, which is why nanoscale driver-follower systems have not been realized. Here, we describe bottom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…We have here used an external electric field to drive the rotor out of equilibrium, as this approach is comparatively easy to implement experimentally. One of the major challenges for future work will be realization of out-of-equilibrium systems by other means, in particular Brownian motors that are fueled by chemical reactions [34, 35].…”
Section: Discussionmentioning
confidence: 99%
“…We have here used an external electric field to drive the rotor out of equilibrium, as this approach is comparatively easy to implement experimentally. One of the major challenges for future work will be realization of out-of-equilibrium systems by other means, in particular Brownian motors that are fueled by chemical reactions [34, 35].…”
Section: Discussionmentioning
confidence: 99%
“…Instead, we have to make a decision about whether to accept or reject them. 52 That decision can be complex and emotional, and is often guided by what people in our relevant social networks do, e.g. how many adopt those ideas and behaviours and how many resist them.…”
Section: Complex Contagionmentioning
confidence: 99%
“…However, in complex contagion, Centola has found that strong ties are in fact essential for the spread of ideas, behaviours, and norms, precisely because their adoption requires social confirmation from multiple sources. 56 People are less willing to adopt them unless there is sufficient reinforcement from more than one person in their relevant network. Centola identifies four social mechanisms underpinning these phenomena:…”
Section: Complex Contagionmentioning
confidence: 99%
“…(iii) Vesicles containing DNA nanostructures have so-far been demonstrated in equilibrium, which is not consistent with sustaining life. While chemical fuelling of DNA nanostructures has been demonstrated [31][32][33], it requires chemical functionalization or DNA strand displacement reactions [34]. (iv) Finally, the implementation of evolution is not straightforward.…”
Section: Introductionmentioning
confidence: 99%